The possibilities of decarbonization in wooden housing construction - Pechenkina, Vera; Fatkulina- Yaskova, Lyudmila; Medvedev, Sergey (project baikal, 2025)
The article discusses the use of the “Green” standard for individual housing construction for the design of a wooden house-transformer using double-beam technology to improve the energy efficiency of the house and the assessment of savings in investment and operating costs, including through energy savings during operation, as well as the calculation of the potential for reducing CO2 emissions, including the use of alternative energy sources and tools for motivating their use in Siberia.
Keywords: wooden housing construction; energy-efficient transformable house; green standard of individual housing construction; decarbonization; CO2 emissions